Barriers to Screening for Gestational Diabetes Mellitus in New Zealand Following the Introduction of Universal Screening Recommendations - Lynne Chepulis; Valentina Papa; Brittany Morison; Shemana Cassim; Ruth Martis (Mary Ann Liebert, 2022)
Background: In 2014 the New Zealand Ministry of Health implemented a universal program of screening for gestational diabetes mellitus (GDM) in pregnancy; however, data suggest that only half of all women are being screening according to the guidelines. This study aimed to explore women's views and experiences of GDM screening and to determine what the main screening barriers are. Methods: Eighteen women were recruited from the Waikato region of New Zealand, who were either pregnant (>28 weeks of gestation) or had given birth in the last 6 months. These women participated in a semi-structured interview about their experience of GDM screening and the transcripts were thematically analyzed. Of these women, 14 had been screened for gestational diabetes (three were screened late) and four had not been screened at all. Results: Multiple barriers to screening for GDM were identified, with two overarching themes of ?confusion, concerns, and access to information for screening,? and ?challenges to accessing and completing the screening test.? Specific barriers included the preference of risk-based assessments for GDM by their leading health professional (usually a registered midwife); negative perceptions of ?sugar drink test?; needing time off work and childcare; travel costs for rural women; previous negative screening experiences; and reduced health literacy. Conclusion: There appear to be both woman-, midwife-, and system-level barriers to screening for GDM. While screening is ultimately a woman's choice, there does appear to be capacity to increase screening rates by improving awareness of the updated guidelines, and making the test environment more accessible and comfortable.